Counterfactual conditionals and dynamic laws - Schulz, Katrin (Proceedings of the Amsterdam Colloquium, 2007)
In this paper we will argue that in order to account for the meaning of counterfactual conditionals we need to refer to and distinguish between static (f.i. analytical) laws and dynamic (f.i. causal) laws. We will propose an approach that combines premise semantics for counterfactuals in the style of Veltman 2005 with a representation of causal dependencies based on Pearl 2000.